Cross-Leg as Salvage Procedure after Free Flaps Transfer Failure: A Case Report. (29th March 2012) - Contedini, F.; Negosanti, L.; Fabbri, E.; Pinto, V.; Tavaniello, B.; Sgarzani, R.; Cipriani, R.
Abstract : Posttraumatic wounds of the lower leg with soft tissue defects and exposed fractures are a reconstructive challenge due to the scarce availability of local tissues and recipient vessels. Even when a free tissue transfer can be performed the risk of failure remains considerable. When a free flap is contraindicated or after a free flap failure, the cross-leg flap is still nowadays a possible option. We report a case of a male with a severe posttraumatic wound of the lower leg with exposed tibia fracture firstly treated with two consecutive latissimus dorsi muscular free flaps, failed for vascular thrombosis; the coverage was then achieved with a cross-leg flap with acceptable results.